V. S. Nersesyants’ Political and Legal Ideas about the Rule of Law State and Their Reflection in the Constitution of the Russian Federation and the Constitution of the Republic of Armenia - Panchenko, Vladislav; Makarchuk, Ivan; Vlasenko, Valery; Alekseeva, Nadezhda; Frolova, Natalya (Տիգրան Մեծ)
Since the inception of the idea of the rule of law state, the problems of its formation and development have always been in the focus of attention of progressive countries, as well as humanities scholars. During the years of perestroika, for the purposes of prospective legal construction, V. S. Nersesyants formulated the distinctive features and components of the rule of law state, without which the existence of the rule of law state is impossible. Well-known historical events led to the beginning of the formation of a new legal space on the territory of the Russian Federation and the Republic of Armenia, which is primarily due to the adoption of basic laws - the Constitutions of these countries. This article examines the political and legal views of V. S. Nersesyants about the rule of law state. The analysis revealing the reflection of his ideas in the Constitution of the Russian Federation and the Constitution of the Republic of Armenia is carried out.
Keywords: Constitution of the Russian Federation; Philosophy of Law